2014
DOI: 10.1021/om500411b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Boron-Fused 1,4-Dithiin via Cobalt-Mediated Disulfuration of Alkyne at the o-Carborane-9,12-dithiolate Unit

Abstract: We present the first synthesis and characterization of a series of boron-fused 1,4-dithiin compounds through the reactions of newly established boron-substituted 16e half-sandwich complex Cp*Co(9,12-S 2 C 2 B 10 H 10 ) with alkynes. The generated C 2 S 2 B 2 ring in these 1,4-dithiin species is a stable structural motif with electron-negative sulfur atoms, as evidenced by theoretical calculation and its solid-state self-assembly. Single-crystal X-ray analysis indicates that C carb −H•••S hydrogen bonding is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Similar cobalt(III) complex with cyclopentadienyl ligand [Cp*Co{9,12-S2C2B10H10}] was isolated and structurally characterized [152]. This complex is built similarly to the previously discussed rhodium(III) and iridium(III) complexes (see Figure 31).…”
Section: Derivatives With B-hal Bondsmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar cobalt(III) complex with cyclopentadienyl ligand [Cp*Co{9,12-S2C2B10H10}] was isolated and structurally characterized [152]. This complex is built similarly to the previously discussed rhodium(III) and iridium(III) complexes (see Figure 31).…”
Section: Derivatives With B-hal Bondsmentioning
confidence: 63%
“…It was found that [Cp*Ir{9,10-S2C2B10H10}] reacts with phosphine ligands L (L = Ph3P, Me2PhP, MePh2P, Ph2PCH2PPh2) in dichloromethane at room temperature to give complexes [Cp*Ir(L){9,10-S2C2B10H10}]. At the same time, the reaction of [Cp*Ir{9,10-S2C2B10H10}] with dppe leads to the formation of a corresponding dimeric complex [Cp*Ir(Ph2PCH2){9,10-S2C2B10H10}]2 (Figure32b), where CH…HB, CH…B, CH…S, CH…HC, and BH…π intermolecular interactions are observed[151].Similar cobalt(III) complex with cyclopentadienyl ligand [Cp*Co{9,12-S2C2B10H10}] was isolated and structurally characterized[152]. This complex is built similarly to the previously discussed rhodium(III) and iridium(III) complexes (see Figure31).…”
mentioning
confidence: 96%
“…Huge steric hindrance arisen from o-methylphenyl and o-carboranyl groups can even block the formation of corresponding diarylated ocarbobane derivatives. (3) The preference of arylation/diarylation at B(4)/B (5) sites in o-carbobanes was identified by more positive NPA charge distribution on B(4)/B(5)−Hs in it. Further mechanism and energy calculations verify the regioselectivity results predicted by NBO theory well and hint the regioselectivity of B−H activation here is strikingly affected by electronic effect.…”
Section: Discussionmentioning
confidence: 99%
“…o -Carboranes, with two adjacent B–H vertices in carboranes replaced by C–H units, have potential applications in many a field such as boron neutron capture therapy and drug development. Therefore, the functionalization of o -carboranes has become the focus in carborane area for decades. …”
Section: Introductionmentioning
confidence: 99%
“…The formation of the thiyl radicals is attributed to the existence of the noninnocent sulfur ligands like dithiolenes, which have the ability to delocalize electron density. Similarly, Yan and co-workers adopted [S 2 C 2 (B 10 H 10 )] 2– unit to synthesize Co complexes, which also exhibit sulfur-centered addition of alkynes and can release the alkyne disulfurated products . Unexpectedly, Goh utilized soft thioether-dithiolate tpdt (tpdt = S­(CH 2 CH 2 S – ) 2 ) tridentate ligand to generate the half-sandwich ruthenium complex, which displayed sulfur-based alkylation by electrophilic attack of alkylation agent .…”
Section: Introductionmentioning
confidence: 99%